Cytochrome P450–redox partner fusion enzymes - Munro, Andrew W.; Girvan, Hazel M.; McLean, Kirsty J. (Biochimica et biophysica acta, 2007)
The cytochromes P450 (P450s) are a broad class of heme b-containing mono-oxygenase enzymes. The vast majority of P450s catalyse reductive scission of molecular oxygen using electrons usually derived from coenzymes (NADH and NADPH) and delivered from redox partner proteins. Evolutionary advantages may be gained by fusion of one or more redox partners to the P450 enzyme in terms of e.g. catalytic efficiency. This route was taken by the well characterized flavocytochrome P450 BM3 system (CYP102A1) from Bacillus megaterium, in which soluble P450 and cytochrome P450 reductase enzymes are covalently linked to produce a highly efficient electron transport system for oxygenation of fatty acids and related molecules. However, genome analysis and ongoing enzyme characterization has revealed that there are a number of other novel classes of P450–redox partner fusion enzymes distributed widely in prokaryotes and eukaryotes. This review examines our current state of knowledge of the diversity of these fusion proteins and explores their structural composition and evolutionary origins.